Formation of Thinking and Its Forms - Stoškus, Krescencijus Antanas (Problemos, 1975)
The idea of the existence of different forms (including historical) of thinking is supported by K. Stoškus in his paper. The author thinks that assuming the conception character of thinking in the most wide sense of the word does not exclude the possibility of opposing the image way of thinking to the conceptual one in the narrow logical (or some other) sense of the word. The author tends to think that psychics of the primitive man was not the human psychics in the sense of homo sapiens thinking.